The effectiveness of breakfast time on cognitive function among university students: A cluster experiment study protocol - Dharina Baharuddin; Riza Septiani; Fahrisal Akbar; Naimah Naimah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Breakfast is important for supporting cognitive function. However, national surveys show that around 56% of university students in Indonesia often skip breakfast. Research on the optimal timing of breakfast to enhance cognitive function is limited. This study aims to evaluate the effectiveness of different breakfast times on students’ cognitive abilities and health indicators. Methods: A Cluster Randomized Controlled Trial (CRCT) was conducted at the University of Muhammadiyah Aceh in 2024. A total of 60 students from three faculties were recruited and randomly assigned into three groups: intervention 1 (breakfast at 06:30–07:30), intervention 2 (07:31–08:31), and a control group (usual breakfast habits). The intervention lasted 8 weeks (4 weeks intervention, 4 weeks maintenance). Cognitive function was assessed using the Army Alpha Test, and mood was measured with the Profile of Mood Scales. Data were analyzed based on the Intention-to-Treat (ITT) principle and the Generalized Estimating Equation (GEE) method in SPSS version 25.0. Results: This protocol is designed to explore the most suitable breakfast timing for students. Expected outcomes include identifying breakfast times that significantly enhance cognitive function. Conclusion: The study is expected to provide evidence for designing breakfast interventions that support students’ cognitive function and overall health.